Composite graphene electrode with high specific surface area and preparation and application thereof

By alternately stacking graphene nanofilms and composite film structures, the problem of degradation of specific surface area and conductivity of multi-layer graphene electrodes is solved, and a composite graphene electrode with high specific surface area and high conductivity is achieved, which is suitable for flexible supercapacitors and smart wearable devices.

CN120545102APending Publication Date: 2025-08-26CHONGQING ENERGY COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510745817.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The multilayer graphene electrode has reduced specific surface area and reduced conductivity due to interlayer stacking, which affects its application in high-power scenarios.

Method used

The alternately stacked graphene nanofilms and composite film structures are adopted to improve conductivity, the composite film increases the specific surface area, and a porous structure and a three-dimensional conductive network are formed through the polyimide film to optimize the interlayer binding force.

Benefits of technology

It significantly improves the specific surface area and conductivity of composite graphene electrodes, combines mechanical stability and flexibility, and is suitable for flexible supercapacitors and smart wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of graphene electrodes, and provides a high-specific-surface-area composite graphene electrode and preparation and application thereof.The composite graphene electrode is of a multi-layer structure and comprises a first-stage layer and a second-stage layer which are alternately stacked, the first-stage layer is a graphene nano-film, the second-stage layer is a composite film, and the first-stage layer and the second-stage layer are stacked alternately. Raw materials of the composite film comprise a polyimide film and a graphene dispersion liquid, and the composite film is prepared through a dip-coating method. The composite graphene electrode has high specific surface area and high conductivity, and has wide application prospects in the fields of electrode materials of flexible supercapacitors and intelligent wearable equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of graphene electrodes, and in particular to a high specific surface area composite graphene electrode and its preparation and application. Background Art

[0002] Graphene electrodes usually refer to two-dimensional materials composed of a single layer of carbon atoms, which have high conductivity and ultra-high mechanical strength; while multilayer graphene electrodes usually refer to materials composed of multiple layers of graphene or composites with other materials such as metal oxides, which optimize performance through stacking or doping, such as increasing their specific surface area and improving electrocatalytic activity.

[0003] At present, multilayer graphene electrodes are more practical in the field of industrial energy storage. However, the multilayer graphene sheets in multilayer graphene electrodes are often tightly stacked due to the van der Waals force, resulting in part of the surface being covered by the upper layer, and the actual exposed active surface area is significantly reduced. For example, the theoretical specific surface area of ​​a single layer of graphene can reach 2630m 2 / g, while the measured specific surface area of ​​multilayer graphene may be reduced to below 50%. The interlayer stacking of multilayer graphene electrodes compresses or even closes the micropores that could originally form a double electric layer, weakening the charge storage capacity and indirectly reducing its effective specific surface area. In addition, multilayer graphene electrodes are prone to defects such as wrinkles and cracks during the preparation process. This structure destroys the two-dimensional plane continuity of the sheet, resulting in local areas that cannot contribute to the effective surface area. Furthermore, when the specific surface area of ​​a multilayer graphene electrode decreases, it is often accompanied by interlayer agglomeration or structural defects, such as vacancies and lattice distortion. These defects will introduce additional electron scattering centers, hindering the free movement of carriers, and thus weakening the conductivity of the electrode; or when the specific surface area of ​​a multilayer graphene electrode decreases, its electron transmission path may be compressed, the carrier mobility decreases, and thus weakening the conductivity of the electrode.

[0004] However, the decline in the conductivity of multilayer graphene electrodes may cause chain reactions such as increased internal resistance, power density decay, and deterioration of cycle stability in their application devices, such as supercapacitors and other battery devices, severely limiting their application in high-power scenarios. Summary of the Invention

[0005] In view of the deficiencies in the prior art, the present invention provides a high specific surface area composite graphene electrode and its preparation and application, which can have both high specific surface area and high conductivity.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a high specific surface area composite graphene electrode, which has a multilayer structure, including alternating stacked first-level layers and second-level layers, the first-level layer is a graphene nanofilm, the second-level layer is a composite film, and the raw materials of the composite film include polyimide film and graphene dispersion, which is prepared by dip coating.

[0008] According to the above-mentioned technical means, this application utilizes graphene nanofilm to improve the conductivity of the electrode and serve as the conductive skeleton of the electrode; utilizes composite film to improve the mechanical stability of the electrode and form a three-dimensional conductive network; utilizes the alternating stacking structure of the first-level layer and the second-level layer to form vertical channels. Compared with the single-layer graphene electrode, the electron mobility is reduced to achieve mechanical flexibility.

[0009] Furthermore, the present application utilizes polyimide film and graphene dispersion to prepare a composite film. During this process, the polyimide film can form a porous structure, increasing its porosity and forming an interpenetrating network with graphene, thereby increasing the active area of ​​the electrode and improving its specific surface area. Furthermore, this alternating stacking structure of the composite graphene electrode of the present application can play a synergistic role, balancing its conductivity and mechanical strength, optimizing the interfacial bonding between layers, and reducing defects such as cracks and bubbles.

[0010] Furthermore, the graphene nanofilm is a multi-layer stacked structure, and the raw material of the graphene nanofilm includes an ethanol dispersion containing graphene oxide sheets, which is prepared by directed self-assembly.

[0011] Furthermore, the thickness ratio of the first level layer to the second level layer is 1:(0.5-1).

[0012] Furthermore, the number of alternating stacking is 5 to 20 times.

[0013] Furthermore, the performance of the composite graphene electrode satisfies at least one of the following properties (a) to (c):

[0014] (a) The specific surface area of ​​the composite graphene electrode is 500 m 2 / g~800m 2 / g;

[0015] (b) The conductivity of the composite graphene electrode is 5000 S / m to 5250 S / m;

[0016] (c) The electron mobility of the composite graphene electrode is 5000 cm 2 / V·s~6500cm 2 / V·s.

[0017] A second aspect of the present invention provides a method for preparing a high specific surface area composite graphene electrode, comprising the following steps:

[0018] (1) subjecting the pretreated graphene powder to an oxidation reaction to prepare graphene oxide;

[0019] (2) ultrasonically exfoliating the graphene oxide to obtain graphene oxide sheets;

[0020] (3) deacidifying the graphene oxide sheet, and adding ethanol after deacidification to prepare an ethanol dispersion containing the graphene oxide sheet;

[0021] (4) performing directed self-assembly on the ethanol dispersion to prepare a graphene nanofilm;

[0022] (5) using polyimide film, graphene dispersion and polyethylene terephthalate as raw materials, preparing a three-material composite film by a dip coating method, and then removing the polyethylene terephthalate in the three-material composite film to obtain a composite film;

[0023] (6) Graphene nanofilms and composite films are stacked alternately to prepare a high specific surface area composite graphene electrode.

[0024] Furthermore, in step (4), the ethanol dispersion is driven to undergo directed self-assembly based on the Marangoni effect to form a multilayer stacked graphene nanofilm, wherein the volume ratio of ethanol to deionized water used in the directed self-assembly process is (3 to 5): (3 to 7), and the transfer rate is 0.1 mL / min to 0.5 mL / min.

[0025] Furthermore, in step (5), the polyimide film is a polyimide film that has undergone hydrophilic surface modification treatment.

[0026] Furthermore, step (5) further includes:

[0027] The polyimide film is immersed in a graphene dispersion liquid with polyethylene terephthalate as a substrate to obtain a liquid film, wherein the immersion speed is 25 mm / s to 55 mm / s;

[0028] After the dip coating is completed, the liquid film is picked up to prepare a three-material composite film, wherein the picking-up speed is 10 mm / s to 30 mm / s.

[0029] The third aspect of the present invention provides an application of a high specific surface area composite graphene electrode, which is used as an electrode material for a flexible supercapacitor in smart wearable devices, wherein the composite graphene electrode is the above-mentioned high specific surface area composite graphene electrode, or the composite graphene electrode is prepared according to the above-mentioned method.

[0030] The beneficial technical effects of the present invention are:

[0031] The composite graphene electrode of the present invention utilizes the graphene nanofilm of the first layer to improve the conductivity of the electrode, utilizes the composite film of the second layer to increase the specific surface area of ​​the electrode, utilizes the alternating stacking structure to play a synergistic role, balances its conductivity and mechanical strength, optimizes the interface bonding force between layers, and reduces defects such as cracks and bubbles;

[0032] The preparation method of the composite graphene electrode of the present invention can significantly improve the specific surface area and comprehensive performance of the electrode, and has both high specific surface area and high conductivity. It has broad application prospects in the field of electrode materials for flexible supercapacitors and smart wearable devices. DETAILED DESCRIPTION

[0033] Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention pertains. It should be understood that certain features of the present invention (described in the context of separate embodiments for clarity) may also be provided in combination in a single embodiment. On the contrary, a plurality of features of the present invention (described in the context of a single embodiment for brevity) may also be provided separately or in any suitable combination or in any other described embodiment of the present invention when appropriate. Certain features described in the context of various embodiments will not be considered as essential features of those embodiments unless the embodiment is inoperable without those elements. The present invention will be further described below by specific examples, but it should be noted that the specific process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and substance of the present invention should be included within the scope of protection of the present invention.

[0034] First of all, it should be noted that the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0035] The present invention provides a method for preparing a high specific surface area composite graphene electrode, comprising the following steps:

[0036] (1) The pretreated graphene powder is subjected to an oxidation reaction to prepare graphene oxide.

[0037] Specifically, the pretreatment method in this step is as follows:

[0038] 1) Cleaning the graphene powder: The graphene powder was mixed with an ethanol solution (ethanol-water solution with a volume ratio of 2:1) in a mass ratio of (1-1.5): (3-4.5), and stirred continuously for 4 hours using a magnetic stirrer to complete the cleaning of the graphene powder. In this step, the graphene powder was evenly dispersed, the impurity residue rate was low, and the cleaning efficiency was high;

[0039] 2) pouring the mixture of the washed graphene powder and the ethanol solution into a suction filtration bottle, and filtering the suction filtration bottle using a vacuum filter, wherein an organic filter membrane (such as a PTFE membrane) with a pore size of ≤10 μm is selected to prevent the graphene powder from penetrating the filter membrane;

[0040] 3) The wet graphene powder after filtration was taken out and placed on a glue drying table for drying at 100° C. for 2 h.

[0041] Specifically, the oxidation method in this step is as follows:

[0042] Prepare a mixed acid solution: Prepare 10 mL of dilute nitric acid (concentrated nitric acid and deionized water in a 1:1 volume ratio) in an ice-water bath. Then slowly add 30 mL of concentrated sulfuric acid to the dilute nitric acid in 3 to 5 portions while stirring continuously. During this process, the temperature is controlled at 0°C to 5°C to obtain a mixed acid solution.

[0043] The dried graphene powder was added to a three-necked flask, and potassium permanganate as an oxidant was weighed, wherein the molar ratio of graphene powder to potassium permanganate was 1:3. Mixed acid was added to the three-necked flask, and potassium permanganate was added in three portions. During this process, the temperature was controlled at 70°C to control the oxidation rate, thereby increasing the continuity and uniformity of the oxidation reaction and preventing carbonization of the graphene due to a sudden temperature rise;

[0044] Then, hydrogen peroxide is used to reduce the unreacted potassium permanganate, and a large amount of deionized water is added during the reaction. The product is filtered, washed, and dried to obtain graphene oxide.

[0045] (2) The graphene oxide is subjected to ultrasonic exfoliation to obtain graphene oxide sheets.

[0046] Specifically, in this step, an ultrasonic instrument is used to ultrasonically exfoliate the graphene oxide. During this process, 0.1wt% to 0.5wt% of a surfactant, sodium dodecylbenzenesulfonate, is added to the graphene oxide to improve the dispersion stability of the graphene oxide. During the ultrasonic exfoliation process, the amplitude of the ultrasonic instrument is 30μm to 50μm, the ultrasonic frequency is 60kHz, the ultrasonic time is 10h, the clean water is changed every 1h, and the temperature is controlled below 50°C during the entire process to avoid excessive exfoliation and breakage of the graphene oxide sheets, resulting in poor exfoliation effect.

[0047] (3) The graphene oxide sheet is subjected to deacidification treatment, and after deacidification, ethanol is added to prepare an ethanol dispersion containing the graphene oxide sheet.

[0048] Specifically, in this step, a centrifuge is used to deacidify the graphene oxide sheets, the centrifugation time is 5 minutes, the rotation speed is 5000-7000 rpm, and after the centrifugation is completed, the upper acid solution is removed, and ethanol is added and ultrasonicated, and the above steps are repeated until the pH of the solution is neutral, wherein the ultrasonic time is 10 minutes to 15 minutes, and the mass ratio of the graphene oxide sheets to ethanol is 1: (50-80) to effectively remove the residual acid.

[0049] (4) The ethanol dispersion is subjected to directed self-assembly to prepare a graphene nanofilm.

[0050] Specifically, in this step, the ethanol dispersion is driven to undergo directed self-assembly based on the Marangoni effect to form a multilayer stacked structure of graphene nanofilms, wherein the volume ratio of ethanol to deionized water used in the directed self-assembly process is (3-5): (3-7), and the transfer rate is 0.1 mL / min to 0.5 mL / min.

[0051] More specifically, in this step, the ethanol dispersion is ultrasonicated for 30 minutes at an ultrasonic power of 300W and the temperature is controlled to be room temperature to avoid graphene agglomeration and destruction of the graphene structure; the ethanol dispersion is then transferred from a low surface tension region (ethanol: surface tension of about 22 mN / m) to a high surface tension region (water: 72 mN / m), wherein,

[0052] In this step, a precision pipette pump or an electric translation stage is used to control the transfer rate to 0.1 mL / min to 0.5 mL / min. Too fast a transfer may result in an uneven film, while too slow a transfer may affect the efficiency. The volume ratio of ethanol to deionized water is (3 to 5): (3 to 7) to form a sufficient surface tension gradient to promote self-assembly.

[0053] Next, the film was placed in an environment with a humidity of <40% for 1 to 2 hours to allow the ethanol to evaporate and form a graphene nanofilm. The surface of the graphene nanofilm was gently rinsed three times with ultrapure water to remove residual surfactant (the aforementioned sodium dodecylbenzenesulfonate). The graphene nanofilm was transferred to a substrate (copper foil was selected in this case) and dried for later use.

[0054] (5) Using polyimide film, graphene dispersion and polyethylene terephthalate as raw materials, a three-material composite film is prepared by a dip coating method, and then the polyethylene terephthalate in the three-material composite film is removed to obtain a composite film.

[0055] Specifically, in this step, the polyimide film is a polyimide film that has undergone hydrophilic surface modification treatment (an existing commercial product is purchased, and the manufacturer and type are not specifically limited).

[0056] More specifically, in this step, the polyimide film is immersed in a graphene dispersion (an existing commercial product containing a dispersant, such as WJ-WG01 and Aladdin's graphene dispersion) with polyethylene terephthalate (an existing commercially available product, with no specific limitation on the manufacturer and type) as a substrate to obtain a liquid film, wherein the immersion speed is 25 mm / s to 55 mm / s; after the dipping is completed, the liquid film is picked up to prepare a three-material composite film, wherein the picking-up speed is 10 mm / s to 30 mm / s.

[0057] Next, in order to ensure a tight bond between the polyimide film and the graphene nanofilm, the three-material composite film was dried at 80°C for 30 minutes. Due to the difference in thermal expansion coefficient, polyethylene terephthalate produced micro-interface separation with the polyimide film. The dried three-material composite film was immersed in an ethanol solution (concentration ≥ 95%) for 5 to 10 minutes to ensure that the solvent fully penetrated the interface. A flexible scraper was used to gently scrape the film to assist in the separation of the starting end of the peeling, and the polyethylene terephthalate substrate was removed to obtain a composite film.

[0058] (6) Graphene nanofilms and composite films are stacked alternately to prepare a high specific surface area composite graphene electrode.

[0059] Specifically, in this step, the graphene nanofilm and the composite film are alternately stacked by transfer printing, wherein the thickness ratio of the graphene nanofilm and the composite film is 1:(0.5~1), and the number of alternating stackings is 5 to 20 times. Then, processing and packaging are performed to prepare a high specific surface area composite graphene electrode.

[0060] The present invention also provides a high specific surface area composite graphene electrode, which has a multilayer structure, including alternately stacked first-level layers and second-level layers, the first-level layer is a graphene nanofilm, the second-level layer is a composite film, and the raw materials of the composite film include polyimide film and graphene dispersion, which is prepared by dip coating.

[0061] Furthermore, the present application utilizes graphene nanofilms to improve the conductivity of the electrode and serve as the conductive skeleton of the electrode; utilizes composite films to improve the mechanical stability of the electrode and form a three-dimensional conductive network; utilizes the alternating stacking structure of the first and second layers to form vertical channels. Compared with single-layer graphene electrodes, the electron mobility is reduced while maintaining mechanical flexibility.

[0062] Furthermore, the present application utilizes polyimide film and graphene dispersion to prepare a composite film. During this process, the polyimide film can form a porous structure, increasing its porosity and forming an interpenetrating network with graphene, thereby increasing the active area of ​​the electrode and improving its specific surface area. Furthermore, this alternating stacking structure of the composite graphene electrode of the present application can synergistically balance its conductivity and mechanical strength, optimize the interfacial bonding between layers, and reduce defects such as cracks and bubbles.

[0063] Furthermore, the polyimide film of the present application has both high strength and flexibility, adapts to assembly requirements, and is easy to process and form. It can provide stable support for the graphene nanofilm to prevent it from being damaged or deformed during preparation, transfer and use; its function is to support and protect the graphene nanofilm, enhance its flexibility, so that it can adapt to complex surfaces and movements, such as the bending and stretching of human skin, thereby improving the accuracy and stability of signal detection; in addition, the polyimide film also helps to improve conductivity and signal transmission performance.

[0064] Furthermore, the graphene nanofilm is a multi-layer stacked structure, and the raw material of the graphene nanofilm includes an ethanol dispersion containing graphene oxide sheets, which is prepared by directed self-assembly.

[0065] Furthermore, the thickness ratio of the first level layer to the second level layer is 1:(0.5-1).

[0066] Furthermore, the number of alternating stacking is 5 to 20 times.

[0067] Furthermore, the performance of the composite graphene electrode satisfies at least one of the following properties (a) to (c):

[0068] (a) The specific surface area of ​​the composite graphene electrode is 500 m 2 / g~800m 2 / g;

[0069] (b) The conductivity of the composite graphene electrode is 5000 S / m to 5250 S / m;

[0070] (c) The electron mobility of the composite graphene electrode is 5000 cm 2 / V·s~6500cm 2 / V·s.

[0071] Furthermore, the surface of the composite graphene electrode of the present application is smooth and flat and the contact is tight; and the composite graphene electrode uses the graphene nanofilm of the first layer to improve the conductivity of the electrode, uses the composite film of the second layer to increase the specific surface area of ​​the electrode, and uses its alternating stacking structure to play a synergistic role, balance its conductivity and mechanical strength, optimize the interface bonding force between layers, and reduce defects such as cracks and bubbles.

[0072] Furthermore, the composite graphene electrode of the present application can balance its conductivity and mechanical flexibility, is flexible and thin, is suitable for large-scale production, simplifies the preparation process, and reduces costs.

[0073] The present invention also provides an application of a high specific surface area composite graphene electrode, which is used as an electrode material for a flexible supercapacitor in smart wearable devices, wherein the composite graphene electrode is the above-mentioned high specific surface area composite graphene electrode, or the composite graphene electrode is prepared according to the above-mentioned method.

[0074] The present invention is described in detail below by way of specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, and those skilled in the art can make selections within a suitable range through the description herein, and are not to be limited to the specific numerical values ​​exemplified below.

[0075] Example 1

[0076] (1) Cleaning the graphene powder: The graphene powder was mixed with an ethanol solution (ethanol-water solution with a volume ratio of 2:1) in a mass ratio of 1:3, and stirred continuously for 4 h using a magnetic stirrer to complete the cleaning of the graphene powder;

[0077] The mixed solution of the washed graphene powder and the ethanol solution is poured into a suction filtration bottle, and the suction filtration bottle is filtered using a vacuum filter, wherein a PTFE membrane with a pore size of ≤10 μm is selected;

[0078] The wet graphene powder after filtration was taken out and placed on a glue drying table for drying at 100°C for 2 h.

[0079] Prepare a mixed acid solution: Prepare 10 mL of dilute nitric acid (concentrated nitric acid and deionized water in a 1:1 volume ratio) in an ice-water bath. Then slowly add 30 mL of concentrated sulfuric acid to the dilute nitric acid in three portions while stirring continuously. During this process, the temperature is controlled at 5°C to obtain a mixed acid solution.

[0080] The dried graphene powder was added to a three-necked flask, and potassium permanganate (an oxidant) was weighed. The molar ratio of graphene powder to potassium permanganate was 1:3. Mixed acid was added to the three-necked flask, and potassium permanganate was added in three portions. The temperature was controlled at 70°C during the process.

[0081] Then, hydrogen peroxide is used to reduce the unreacted potassium permanganate, and a large amount of deionized water is added during the reaction. The product is filtered, washed, and dried to obtain graphene oxide.

[0082] (2) An ultrasonic instrument is used to ultrasonically exfoliate the graphene oxide. During this process, 0.5 wt % of a surfactant, sodium dodecylbenzenesulfonate, is added to the graphene oxide. During the ultrasonic exfoliation process, the amplitude of the ultrasonic instrument is 50 μm, the ultrasonic frequency is 60 kHz, the ultrasonic time is 10 h, and the water is changed every 1 h. The temperature is controlled below 50° C. during the entire process.

[0083] (3) Deacidification of the graphene oxide sheets was performed using a centrifuge with a centrifugation time of 5 min and a rotation speed of 7000 rpm. After centrifugation, the upper acid solution was removed, and ethanol was added and ultrasonicated. The above steps were repeated until the pH of the solution reached neutrality. The ultrasonication time was 15 min, and the mass ratio of the graphene oxide sheets to ethanol was 1:50.

[0084] (4) The ethanol dispersion was ultrasonicated for 30 min at a power of 300 W and the temperature was controlled at room temperature; then the ethanol dispersion was transferred from the low surface tension region (ethanol: surface tension of about 22 mN / m) to the high surface tension region (water: 72 mN / m), wherein the transfer was controlled by a precision pipette pump at a transfer rate of 0.1 mL / min and a volume ratio of ethanol to deionized water of 3:7;

[0085] Next, the film was placed in an environment with a humidity of <40% for 2 hours to allow the ethanol to evaporate and form a graphene nanofilm. The surface of the graphene nanofilm was gently rinsed three times with ultrapure water to remove residual sodium dodecylbenzenesulfonate. The graphene nanofilm was transferred to a copper foil and dried for later use.

[0086] (5) The polyimide film is immersed in a graphene dispersion liquid with polyethylene terephthalate as the substrate to obtain a liquid film, wherein the immersion speed is 25 mm / s; after the dipping is completed, the liquid film is picked up to prepare a three-material composite film, wherein the picking speed is 10 mm / s;

[0087] Next, in order to ensure a tight bond between the polyimide film and the graphene nanofilm, the three-material composite film was dried at 80°C for 30 minutes. Due to the difference in thermal expansion coefficient, polyethylene terephthalate produced micro-interface separation with the polyimide film. The dried three-material composite film was immersed in an ethanol solution (concentration ≥ 95%) for 8 minutes to ensure that the solvent fully penetrated into the interface. A flexible scraper was used to gently scrape the film to assist in the separation of the starting end of the peeling, and the polyethylene terephthalate substrate was removed to obtain a composite film.

[0088] (6) The graphene nanofilm and the composite film are alternately stacked by the transfer printing method, wherein the thickness ratio of the graphene nanofilm and the composite film is 1:1, and the number of alternating stackings is 5 times. Then, the electrodes are processed and packaged to prepare a composite graphene electrode with a high specific surface area.

[0089] Example 2

[0090] The difference between this embodiment and embodiment 1 is that:

[0091] (4) The ethanol dispersion was ultrasonicated for 30 min at a power of 300 W and the temperature was controlled at room temperature; then the ethanol dispersion was transferred from the low surface tension region (ethanol: surface tension of about 22 mN / m) to the high surface tension region (water: 72 mN / m), wherein the transfer was controlled by a precision pipette pump at a transfer rate of 0.5 mL / min and a volume ratio of ethanol to deionized water of 3:7;

[0092] Next, the film was placed in an environment with a humidity of <40% for 2 hours to allow the ethanol to evaporate and form a graphene nanofilm. The surface of the graphene nanofilm was gently rinsed three times with ultrapure water to remove residual sodium dodecylbenzenesulfonate. The graphene nanofilm was transferred to a copper foil and dried for later use.

[0093] Example 3

[0094] The difference between this embodiment and embodiment 1 is that:

[0095] (5) The polyimide film is immersed in a graphene dispersion liquid with polyethylene terephthalate as the substrate to obtain a liquid film, wherein the immersion speed is 55 mm / s; after the dip coating is completed, the liquid film is picked up to prepare a three-material composite film, wherein the picking up speed is 30 mm / s;

[0096] Next, in order to ensure a tight bond between the polyimide film and the graphene nanofilm, the three-material composite film was dried at 80°C for 30 minutes. Due to the difference in thermal expansion coefficient, polyethylene terephthalate produced micro-interface separation with the polyimide film. The dried three-material composite film was immersed in an ethanol solution (concentration ≥ 95%) for 10 minutes to ensure that the solvent fully penetrated the interface. A flexible scraper was used to gently scrape the film to assist in the separation of the starting end of the peeling, and the polyethylene terephthalate substrate was removed to obtain a composite film.

[0097] Example 4

[0098] The difference between this embodiment and embodiment 1 is that:

[0099] (6) The graphene nanofilm and the composite film are alternately stacked by the transfer printing method, wherein the thickness ratio of the graphene nanofilm and the composite film is 1:1, and the number of alternating stackings is 15 times. Then, the electrodes are processed and packaged to prepare a composite graphene electrode with a high specific surface area.

[0100] Example 5

[0101] The difference between this embodiment and embodiment 1 is that:

[0102] (6) The graphene nanofilm and the composite film are alternately stacked by the transfer printing method, wherein the thickness ratio of the graphene nanofilm and the composite film is 1:0.5, and the number of alternating stackings is 20 times. Then, the electrodes are processed and packaged to prepare a composite graphene electrode with a high specific surface area.

[0103] Comparative Example 1

[0104] The difference between this comparative example and Example 4 is:

[0105] (5) The polydimethylsiloxane film is immersed in a graphene dispersion with polyethylene terephthalate as a substrate to obtain a liquid film, wherein the immersion speed is 40 mm / s; after the dip coating is completed, the liquid film is picked up to prepare a three-material composite film, wherein the picking-up speed is 25 mm / s;

[0106] Next, in order to ensure a tight bond between the polydimethylsiloxane film and the graphene nanofilm, the three-material composite film was dried at 70°C for 40 minutes, and the dried three-material composite film was immersed in an ethanol solution (concentration ≥ 95%) for 15 minutes to ensure that the solvent fully penetrated into the interface. A flexible scraper was used to gently scrape the film to assist in the separation of the starting end of the peeling, remove the polyethylene terephthalate substrate, and obtain a composite film.

[0107] Comparative Example 2

[0108] The difference between this comparative example and Example 4 is:

[0109] (1) Cleaning the graphene powder: The graphene powder was mixed with an ethanol solution (ethanol-water solution with a volume ratio of 2:1) in a mass ratio of 1:3, and stirred continuously for 4 h using a magnetic stirrer to complete the cleaning of the graphene powder;

[0110] The mixed solution of the washed graphene powder and the ethanol solution is poured into a suction filtration bottle, and the suction filtration bottle is filtered using a vacuum filter, wherein a PTFE membrane with a pore size of ≤10 μm is selected;

[0111] The wet graphene powder after filtration was taken out and placed on a glue drying table for drying at 100° C. for 2 h to obtain graphene.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 4 is:

[0114] (1) Cleaning the graphene powder: The graphene powder was mixed with an ethanol solution (ethanol-water solution with a volume ratio of 2:1) in a mass ratio of 1:3, and stirred continuously for 4 h using a magnetic stirrer to complete the cleaning of the graphene powder;

[0115] The mixed solution of the washed graphene powder and the ethanol solution is poured into a suction filtration bottle, and the suction filtration bottle is filtered using a vacuum filter, wherein a PTFE membrane with a pore size of ≤10 μm is selected;

[0116] The wet graphene powder after filtration was taken out and placed on a glue drying table for drying at 100°C for 2 h.

[0117] The dried graphene powder was added to a three-necked flask, and potassium permanganate as an oxidant was weighed, wherein the molar ratio of graphene powder to potassium permanganate was 1:3. 30 mL of concentrated nitric acid was added to the three-necked flask in three portions, during which the temperature was controlled at 0°C. Potassium permanganate was also added in three portions, during which the temperature was controlled at 70°C.

[0118] Then, hydrogen peroxide is used to reduce the unreacted potassium permanganate, and a large amount of deionized water is added during the reaction. The product is filtered, washed, and dried to obtain graphene oxide.

[0119] Comparative Example 4

[0120] The difference between this comparative example and Example 4 is:

[0121] (6) The graphene nanofilm and the composite film are alternately stacked by the transfer printing method, wherein the thickness ratio of the graphene nanofilm and the composite film is 0.5:1, and the number of alternating stackings is 10 times. Then, the electrodes are processed and packaged to prepare a composite graphene electrode with a high specific surface area.

[0122] Comparative Example 5

[0123] The difference between this comparative example and Example 4 is:

[0124] (2) Deacidification of graphene oxide was performed using a centrifuge with a centrifugation time of 5 min and a rotation speed of 5000 rpm. After centrifugation, the upper acid solution was removed, and ethanol was added and ultrasonicated. The above steps were repeated until the pH of the solution reached neutrality. The ultrasonication time was 15 min, and the mass ratio of graphene oxide to ethanol was 1:50.

[0125] Performance testing

[0126] Conductivity: The conductivity of the composite graphene electrodes of various embodiments and comparative examples was tested by a four-probe method. The results are shown in Table 1.

[0127] Electrode thickness: According to GB / T 40066-2021, the electrode thickness of the composite graphene electrode of each embodiment and each comparative example was measured by atomic force microscopy. The results are shown in Table 1.

[0128] Electron mobility: The electron mobility of the composite graphene electrodes of each embodiment and each comparative example was tested by a four-probe method. The results are shown in Table 1.

[0129] Resistivity: The resistivity of the composite graphene electrodes of various embodiments and comparative examples was measured using a four-probe method. The results are shown in Table 1.

[0130] Current density: The current density of the composite graphene electrodes of each embodiment and each comparative example was tested using a field effect transistor (FET). The results are shown in Table 1.

[0131] Specific surface area: The specific surface area of ​​the composite graphene electrodes of each embodiment and each comparative example was measured by nitrogen adsorption-desorption method (BET method). The results are shown in Table 1.

[0132] The experimental data and analysis are as follows:

[0133] Table 1 Performance of composite graphene electrodes in various embodiments and comparative examples

[0134]

[0135] As can be seen from Table 1, the composite graphene electrodes prepared in each embodiment of the present application can improve the mechanical stability of the electrode and form a three-dimensional conductive network; and their alternating stacking structure, compared with the composite graphene electrodes in each comparative example, has a reduced electron mobility while also having mechanical flexibility. Moreover, the composite graphene electrodes prepared in each embodiment of the present application have improved conductivity, electrode thickness, and specific surface area compared with the composite graphene electrodes in each comparative example. Therefore, under the premise of the above performance parameters and combined with their current carrying density, the composite graphene electrodes prepared in each embodiment of the present application have excellent mechanical flexibility, mechanical stability, and conductivity balance, and can be used as electrode materials for flexible supercapacitors in smart wearable devices.

[0136] However, in Comparative Example 1, polydimethylsiloxane film is used to replace the polyimide film, and it is assembled with the graphene nanofilm. The elongation at break of the assembled composite graphene electrode can reach 100% to 300%, which is significantly better than the polyimide film. However, the insulating property of the polydimethylsiloxane film causes the conductive network between the graphene layers to be discontinuous, and the conductive performance is limited. In addition, the long-term temperature resistance upper limit of the polydimethylsiloxane film is 200°C, and it has poor thermal stability and is easily softened and deformed at high temperatures, which limits its application in high-temperature electronic devices. In addition, the conductivity is low, and the conductivity and mechanical flexibility are not as good as the composite graphene electrode in the embodiment of the present application.

[0137] Comparative Example 2 did not oxidize the graphene, resulting in poor subsequent exfoliation and a reduced specific surface area. Unoxidized graphene, due to strong interlayer forces, is prone to fragmentation and edge defects during exfoliation, leading to irregular stacking of the sheets and affecting subsequent self-assembly. The preparation method of Comparative Example 2 significantly reduces the conductivity and mechanical flexibility of the electrode.

[0138] Comparative Example 3 uses a single strong acid to oxidize graphene, which may not effectively introduce sufficient oxygen-containing functional groups, resulting in insufficient interlayer interaction of the graphene oxide and difficulty in peeling; and the peeling efficiency is reduced, the conductivity is significantly reduced, and the mechanical flexibility is deteriorated.

[0139] In Comparative Example 4, after adjusting the thickness ratio and stacking times of the graphene nanofilm and the composite film, the conductivity of the electrode decreased.

[0140] Comparative Example 5 did not exfoliate the graphene oxide, resulting in the dispersion in the subsequent steps containing larger flakes or agglomerates, which in turn affected the subsequent self-assembly process. The directed self-assembly could not form a uniform nanofilm because the graphene oxide flakes were too large or the structure was uneven; and the conductivity was significantly reduced, the specific surface area was reduced, and the mechanical flexibility was deteriorated, making it unsuitable for the field of wearable devices.

[0141] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A high specific surface area composite graphene electrode, characterized in that: The composite graphene electrode is a multilayer structure, including alternately stacked first-level layers and second-level layers, the first-level layer is a graphene nanofilm, the second-level layer is a composite film, and the raw materials of the composite film include polyimide film and graphene dispersion, which are prepared by dip coating.

2. The composite graphene electrode according to claim 1, characterized in that The graphene nanofilm is a multi-layer stacking structure. The raw material of the graphene nanofilm includes an ethanol dispersion containing graphene oxide sheets and is prepared by directed self-assembly.

3. The composite graphene electrode according to claim 1 or 2, characterized in that: The thickness ratio of the first-level layer to the second-level layer is 1:(0.5-1).

4. The composite graphene electrode according to claim 3, characterized in that The number of times of alternating stacking is 5 to 20 times.

5. The composite graphene electrode according to claim 1, 2 or 4, characterized in that: The performance of the composite graphene electrode satisfies at least one of the following performances (a) to (c): (a) The specific surface area of ​​the composite graphene electrode is 500 m 2 / g~800m 2 / g; (b) the electrical conductivity of the composite graphene electrode is 5000 S / m to 5250 S / m; (c) The electron mobility of the composite graphene electrode is 5000 cm 2 / V·s~6500cm 2 / V·s.

6. A method for preparing a high specific surface area composite graphene electrode, characterized in that: The following steps are involved: (1) subjecting the pretreated graphene powder to an oxidation reaction to prepare graphene oxide; (2) ultrasonically exfoliating the graphene oxide to obtain graphene oxide sheets; (3) deacidifying the graphene oxide sheet, and adding ethanol after deacidification to prepare an ethanol dispersion containing the graphene oxide sheet; (4) performing directed self-assembly on the ethanol dispersion to prepare a graphene nanofilm; (5) using a polyimide film, a graphene dispersion, and polyethylene terephthalate as raw materials, preparing a three-material composite film by a dip coating method, and then removing the polyethylene terephthalate from the three-material composite film to obtain a composite film; (6) The graphene nanofilm and the composite film are alternately stacked to prepare a composite graphene electrode with a high specific surface area.

7. The method according to claim 6, characterized in that In the step (4), the ethanol dispersion is driven to perform directed self-assembly based on the Marangoni effect to form the graphene nanofilm with a multilayer stacked structure, wherein the volume ratio of ethanol to deionized water used in the directed self-assembly process is (3-5): (3-7), and the transfer rate is 0.1 mL / min to 0.5 mL / min.

8. The method according to claim 6 or 7, characterized in that In the step (5), the polyimide film is a polyimide film that has undergone hydrophilic surface modification treatment.

9. The method according to claim 8, characterized in that The step (5) further comprises: The polyimide film is immersed in a graphene dispersion liquid with polyethylene terephthalate as a substrate to obtain a liquid film, wherein the immersion speed is 25 mm / s to 55 mm / s; After the dipping is completed, the liquid film is picked up to prepare the three-material composite film, wherein the picking-up speed is 10 mm / s to 30 mm / s.

10. An application of a high specific surface area composite graphene electrode, characterized in that: The composite graphene electrode is used as an electrode material for a flexible supercapacitor and is applied to smart wearable devices, wherein the composite graphene electrode is the high specific surface area composite graphene electrode according to any one of claims 1 to 5, or the composite graphene electrode is prepared according to the method according to any one of claims 6 to 9.